The first national subject benchmark statement for UK higher education in policing: the importance of effective partnership and collaboration - Pepper, Ian; Cox, Carol; Fee, Ruth; Horgan, Shane; Jarman, Rod; Jones, Matthew; Policek, Nicoletta; Rogers, Colin; Tattum, Clive (Higher education, skills and work-based learning, 2024)
PurposeThe Quality Assurance Agency (QAA) for Higher Education in the UK focuses on maintaining, enhancing and standardising the quality of higher education. Of significant impact are the development of subject benchmark statements (SBS) by the QAA, which describe the type and content of study along with the academic standards expected of graduates in specific disciplines. Prior to 2022, the QAA did not have a SBS to which higher education policing programmes could be directly aligned.Design/methodology/approachOver 12-months, a SBS advisory group with representatives from higher education across England, Scotland, Wales and Northern Ireland, The College of Policing, QAA, Police Federation of England and Wales and policing, worked in partnership to harness their collective professional experience and knowledge to create the first UK SBS for policing. Post publication of the SBS, permission was sought and granted from both the College of Policing and QAA for members of the advisory group to reflect in an article on their experiences of collaborating and working in partnership to achieve the SBS.FindingsThere is great importance of creating a shared vision and mutual trust, developed through open facilitated discussions, with representatives championing their cause and developing a collaborative and partnership approach to completing the SBS.Practical implicationsA collaborative and partnership approach is essential in developing and recognising the academic discipline of policing. This necessarily requires the joint development of initiatives, one of which is the coming together of higher education institutions, PSRBs and practitioner groups to collaborate and design QAA benchmark statements.Social implicationsThe SBS advisory group has further driven forward the emergence of policing as a recognised academic discipline to benefit multiple stakeholders.Originality/valueThe SBS for policing is the first across the UK. The authors experiences can be used to assist others in their developments of similar subject specific benchmarking or academic quality standards.